Preparation method and application of PV3Mo9 coupled CuSe-rGO nano composite catalyst
By modifying CuSe nanocomposite catalysts with PV3Mo9 on reduced graphene oxide, the problem of poor controllability of existing catalysts in electrocatalytic CO2 reduction was solved, achieving efficient generation of C2+ products and inhibition of the HER process, thus improving the stability and selectivity of the catalyst.
Patent Information
- Application Number
- CN202411430026.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Existing catalysts have poor controllability in the electrocatalytic CO2 reduction process, and cannot effectively and deeply electroreduc CO2 and increase the formation of C2+ products. In addition, their adsorption capacity for CO is insufficient, which affects the selectivity and efficiency of the reaction.
A PV3Mo9-coupled CuSe@rGO nanocomposite catalyst was prepared by modifying PV3Mo9 onto reduced graphene oxide and combining it with CuSe nanoparticles to optimize the catalyst surface design, thereby enhancing the adsorption capacity and reaction pathway of *CO intermediates and inhibiting the HER process.
The efficiency and selectivity of C2+ product formation were improved, the Faraday efficiency of ethylene reached 75.6%, hydrogen production was significantly reduced, catalyst stability and durability were improved, and efficient electrochemical conversion of CO2 was achieved.
Smart Images

Figure CN119307966A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a catalyst. Background Art
[0002] Current electrocatalytic CO2 reduction (ECO2RR) technology is facing a series of challenges that collectively hinder its industrialization. First, the existence of the hydrogen evolution reaction (HER) affects the C 2+ The Faraday efficiency (FE) of the product is low, which not only weakens the ability to generate high-value products, but also highlights the problem of low energy efficiency. Secondly, the existing catalysts have insufficient adsorption capacity for *CO, which directly limits the activity of the catalyst, thereby affecting the selectivity and efficiency of the reaction. In addition, due to the inert nature of CO2 reduction and the 2+ The reduction pathways of the products are complicated, which means that the ECO2RR process requires not only high energy input, but also highly active catalysts to activate and reduce the energy barrier of the reaction, making economical and efficient conversion particularly difficult. It is worth noting that current research focuses more on the optimization of C1 products, while ignoring C 2+ The products such as C2H4 and C2H5OH have great potential in the industrial field. This research bias not only limits the comprehensiveness of catalyst design and optimization, but also misses the opportunity to explore more efficient and valuable conversion pathways. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that the existing catalyst has poor controllability on the electrocatalytic CO2 reduction technology, and cannot deeply electro-reduce CO2 and increase C 2+ In order to solve the problem of product, a preparation method and application of PV3Mo9 coupled CuSe@rGO nanocomposite catalyst are provided.
[0004] In view of the above problems, the present invention prepares a method of converting H6PV3Mo9O 40 (PV3Mo9)-modified CuSe nanocomposite electrocatalyst supported on reduced graphene oxide (rGO) (PV3Mo9 / CuSe@rGO) achieves efficient regulation of ECO2RR, enhances the electroreduction depth of CO2 and improves C 2+ FE of the product.
[0005] A method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst is specifically completed by the following steps:
[0006] 1. Preparation of polyoxometalate PV3Mo9:
[0007] ①, Na2HPO4 and Na2MoO4 are dissolved in deionized water, heated and stirred until boiling and maintained for a period of time, then NaVO3 aqueous solution is added, refluxed and heated for a period of time, cooled to room temperature, and the pH value of the solution is adjusted to acidic to obtain a reaction solution;
[0008] ② The reaction solution was transferred to a separatory funnel and extracted with anhydrous ether for multiple times. During the extraction process, dilute sulfuric acid was added until the water phase turned yellow, and the precipitated red oil droplets were collected. The extraction was repeated until the water phase turned light yellow, and then the ether was removed in a fume hood, and the polyoxometalate H6PV3Mo9O was obtained by concentration and crystallization. 40 , denoted as PV3Mo9;
[0009] 2. Preparation of Cu2O:
[0010] Cu(NO3)2 is added to ethylene glycol, stirred until completely dissolved, and then transferred to a hydrothermal kettle, heated at 120°C to 160°C for a period of time, and after cooling, the precipitate is separated by suction filtration, and the precipitate is washed and dried to obtain Cu2O;
[0011] 3. Preparation of hollow CuSe:
[0012] ①, add NaBH4 and selenium powder into deionized water, disperse evenly by ultrasonication to obtain solution A;
[0013] ②, dispersing Cu2O in water to obtain a Cu2O aqueous dispersion; adding solution A to the ultrasonically dispersed Cu2O aqueous dispersion, ultrasonically stirring and reacting for a period of time, and then centrifuging to obtain a precipitate; washing the precipitate, and then drying to obtain a hollow CuSe;
[0014] 4. Preparation of PV3Mo9 / CuSe:
[0015] The hollow CuSe is dispersed in water to obtain a hollow CuSe aqueous dispersion; concentrated HCl is added dropwise to the hollow CuSe aqueous dispersion, stirred and reacted for a period of time, and then PV3Mo9 is added, and the stirring and reaction is continued for a period of time, and then centrifuged to obtain a precipitate; the precipitate is washed and then dried to obtain a PV3Mo9 / CuSe powder;
[0016] 5. Preparation of PV3Mo9 / CuSe@rGO:
[0017] ①, dispersing graphene oxide in water to obtain a graphene oxide dispersion;
[0018] ②, dispersing PV3Mo9 / CuSe powder into water to obtain PV3Mo9 / CuSe dispersion;
[0019] ③. Add the graphene oxide dispersion to the PV3Mo9 / CuSe dispersion and stir for a period of time to obtain a mixed solution; heat the mixed solution to 140°C to 160°C and maintain for a period of time, centrifuge and obtain a precipitate; wash the precipitate and dry it to obtain PV3Mo9 / CuSe@rGO, which is a PV3Mo9-coupled CuSe@rGO nanocomposite catalyst.
[0020] Principle of the present invention:
[0021] Currently, ECO2RR is preparing C 2+ The technology of the product is mainly limited by: the target product FE and selectivity; the catalyst's weak adsorption capacity for *CO; and the high applied potential.
[0022] Transition metal chalcogenides, with their unique d-orbital electronic configuration, abundant adjustable active sites and high conductivity, show excellent catalytic performance in ECO2RR. They can not only promote high-value C 2+ The product is highly selective for the target carbon product. By optimizing the catalyst surface design, transition metal selenides such as CuSe can significantly improve the adsorption capacity of the key intermediate *CO, thereby promoting C 2+ The formation of products. However, pure transition metal selenide particles tend to aggregate, which limits their catalytic performance;
[0023] To solve this problem, the present invention introduces rGO as a catalyst carrier material; rGO, with its excellent conductivity, high specific surface area, good chemical stability and adjustable surface properties, effectively reduces the aggregation of transition metal selenide particles and improves the overall performance of the catalyst. By coating the transition metal selenide on carbon cloth and using it as a working electrode, we further enhance the stability and durability of the catalyst;
[0024] At the same time, the introduction of PV3Mo9 as an electrolyte additive not only enhances the system's adsorption capacity for *CO intermediates, but also achieves high adsorption ratio characteristics by retaining more active sites that synergize with PV3Mo9. In addition, the PCET properties of PV3Mo9 help optimize the reaction path, improve the selectivity of the target carbon product, and effectively inhibit HER.
[0025] Based on this, the present invention prepares PV3Mo9 coupled CuSe@rGO nanocomposite catalyst and applies it to ECO2RR system to realize CO2 reduction to prepare C 2+ In the study of products (C2H4, C2H5OH).
[0026] Advantages of the present invention:
[0027] 1. This paper successfully synthesized a new electrocatalyst, PV3Mo9 / CuSe@rGO, and applied it to the field of ECO2RR, focusing on improving C 2+ Product generation efficiency; In this catalytic system, electrochemical coupled conversion of CO2 is achieved, and the HER process is suppressed by finely controlling the applied overpotential to achieve the purpose of improving the selectivity of the target product and FE;
[0028] 2. The present invention proposes a novel method for preparing a highly efficient electrocatalyst. The PV3Mo9 coupled CuSe@rGO nanocomposite catalyst prepared by the method has good uniformity, a safe and environmentally friendly preparation process, no need for complex equipment, simple construction and high cost-effectiveness. At the same time, the prepared catalyst has good stability and is easy to store;
[0029] 3. The PV3Mo9 coupled CuSe@rGO nanocomposite catalyst prepared by the present invention can reduce CO2 to high value-added carbon products: CH3CH2OH, C2H4 and CO when acting on ECO2RR. In this electrolysis system, the FE of ethylene reaches a maximum of 75.6% at –1.2V (vs.RHE);
[0030] 4. When the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst prepared by the present invention acts on ECO2RR, the total FE of the carbon product obtained by reducing CO2 can be maintained above 78% in the entire electrolysis potential range; the FE of hydrogen is controlled below 22% in the entire electrolysis potential range, and the minimum value can reach 2.1% at -1.2V (vs.RHE), which successfully inhibits HER and improves the selectivity of the target product;
[0031] 5. From a microscopic perspective, the present invention designs a CuSe catalyst modified by PV3Mo9 and loaded on rGO to achieve the electroreduction of CO2 to C 2+ The product is liquid-phase product, which is unique and easy to separate; the gas-phase product has high added value and generates high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The scanning electron microscope images of CuSe and PV3Mo9 / CuSe@rGO prepared in Example 1, in which (a) is CuSe, (b) is PV3Mo9 / CuSe@rGO (300nm), and (c) is PV3Mo9 / CuSe@rGO (2μm);
[0033] Figure 2 is the Fourier transform infrared spectra of PV3Mo9 and PV3Mo9 / CuSe@rGO prepared in Example 1;
[0034] Figure 3is the X-ray powder diffraction pattern of PV3Mo9 / CuSe@rGO and CuSe prepared in Example 1;
[0035] Figure 4 The linear voltammetric curve of PV3Mo9 / CuSe@rGO prepared in Example 1 in 0.1M KHCO3 solution under different atmospheres (Ar / CO2);
[0036] Figure 5 is a gas chromatogram of the gas phase product of PV3Mo9 / CuSe@rGO prepared in Example 1 in Application Example 1 after electrolysis at -1.0V (vs.RHE) for 1h;
[0037] Figure 6 is the nuclear magnetic hydrogen spectrum of the cathode liquid of PV3Mo9 / CuSe@rGO prepared in Example 1 in Application Example 1 after electrolysis at -1.0V (vs.RHE) for 1h;
[0038] Figure 7 It is the FE of each product of CuSe, PV3Mo9 / CuSe and PV3Mo9 / CuSe@rGO prepared by Example 1 in Application Examples 1 to 3 after electrolysis for 1 h in the electrolysis range of –0.6 to –1.4 V (vs. RHE), in which (a) is CuSe; (b) is PV3Mo9 / CuSe; (c) is PV3Mo9 / CuSe@rGO;
[0039] Figure 8 It curves obtained after electrolysis of CuSe, PV3Mo9 / CuSe and PV3Mo9 / CuSe@rGO prepared in Example 1 in Examples 1 to 3 at -0.6 to -1.4 V (vs. RHE) for 1 h, in which (a) is CuSe; (b) is PV3Mo9 / CuSe; (c) is PV3Mo9 / CuSe@rGO;
[0040] Fig. 9 This is the AC impedance diagram of PV3Mo9 / CuSe@rGO prepared in Example 1 in 0.1M KHCO3 solution under different atmospheres (Ar / CO2). DETAILED DESCRIPTION
[0041] Specific implementation method 1: This implementation method is a method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst, which is specifically completed by the following steps:
[0042] 1. Preparation of polyoxometalate PV3Mo9:
[0043] ①, Na2HPO4 and Na2MoO4 are dissolved in deionized water, heated and stirred until boiling and maintained for a period of time, then NaVO3 aqueous solution is added, refluxed and heated for a period of time, cooled to room temperature, and the pH value of the solution is adjusted to acidic to obtain a reaction solution;
[0044] ② The reaction solution was transferred to a separatory funnel and extracted with anhydrous ether for multiple times. During the extraction process, dilute sulfuric acid was added until the water phase turned yellow, and the precipitated red oil droplets were collected. The extraction was repeated until the water phase turned light yellow, and then the ether was removed in a fume hood, and the polyoxometalate H6PV3Mo9O was obtained by concentration and crystallization. 40 , denoted as PV3Mo9;
[0045] 2. Preparation of Cu2O:
[0046] Cu(NO3)2 is added to ethylene glycol, stirred until completely dissolved, and then transferred to a hydrothermal kettle, heated at 120°C to 160°C for a period of time, and after cooling, the precipitate is separated by suction filtration, and the precipitate is washed and dried to obtain Cu2O;
[0047] 3. Preparation of hollow CuSe:
[0048] ①, add NaBH4 and selenium powder into deionized water, disperse evenly by ultrasonication to obtain solution A;
[0049] ②, dispersing Cu2O in water to obtain a Cu2O aqueous dispersion; adding solution A to the ultrasonically dispersed Cu2O aqueous dispersion, ultrasonically stirring and reacting for a period of time, and then centrifuging to obtain a precipitate; washing the precipitate, and then drying to obtain a hollow CuSe;
[0050] 4. Preparation of PV3Mo9 / CuSe:
[0051] The hollow CuSe is dispersed in water to obtain a hollow CuSe aqueous dispersion; concentrated HCl is added dropwise to the hollow CuSe aqueous dispersion, stirred and reacted for a period of time, and then PV3Mo9 is added, and the stirring and reaction is continued for a period of time, and then centrifuged to obtain a precipitate; the precipitate is washed and then dried to obtain a PV3Mo9 / CuSe powder;
[0052] 5. Preparation of PV3Mo9 / CuSe@rGO:
[0053] ①, dispersing graphene oxide in water to obtain a graphene oxide dispersion;
[0054] ②, dispersing PV3Mo9 / CuSe powder into water to obtain PV3Mo9 / CuSe dispersion;
[0055] ③. Add the graphene oxide dispersion to the PV3Mo9 / CuSe dispersion and stir for a period of time to obtain a mixed solution; heat the mixed solution to 140°C to 160°C and maintain for a period of time, centrifuge and obtain a precipitate; wash the precipitate and dry it to obtain PV3Mo9 / CuSe@rGO, which is a PV3Mo9-coupled CuSe@rGO nanocomposite catalyst.
[0056] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the mass volume ratio of Na2HPO4, Na2MoO4 and deionized water described in step 1① is (3.2g~3.6g):(21.6g~22.0g):(70mL~90mL); the time of heating and stirring to boiling and maintaining in step 1① is 0.5h~1h; the volume ratio of NaVO3 aqueous solution described in step 1① to deionized water is 20:(70~90); the concentration of NaVO3 aqueous solution described in step 1① is 0.2g / mL~0.3g / mL; the time of reflux heating described in step 1① is 0.5h~1h; the pH value of the solution is adjusted to 2.4~2.6 in step 1①; the volume fraction of dilute sulfuric acid described in step 1② is 50%. The other steps are the same as specific implementation method 1.
[0057] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the mass ratio of Cu(NO3)2 to ethylene glycol in step 2 is 1g:(70mL-90mL); the heating time at 120℃-160℃ in step 2 is 160min-200min; in step 2, the precipitate is washed 3-5 times with anhydrous ethanol, and then dried at 55℃-65℃ for 10h-14h to obtain Cu2O. The other steps are the same as those in specific implementation method one or two.
[0058] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the mass volume ratio of NaBH4, selenium powder and deionized water described in step 3① is (0.03g~0.04g):(0.07g~0.08g):100mL; the concentration of the Cu2O aqueous dispersion described in step 3② is 0.005mol / L~0.015mol / L; the volume ratio of solution A and Cu2O aqueous dispersion described in step 3② is (0.5~1.5):(0.5~1.5); the ultrasonic and stirring reaction time described in step 3② is 0.5h~5h; in step 3②, the precipitate is washed 3 to 5 times with deionized water and anhydrous ethanol in turn, and then dried at 55℃~65℃ for 10h~14h to obtain hollow CuSe. The other steps are the same as specific embodiments 1 to 3.
[0059] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the concentration of the hollow CuSe aqueous dispersion described in step 4 is 0.001 g / mL to 0.002 g / mL; the mass fraction of the concentrated HCl described in step 4 is 36% to 38%; the volume ratio of the concentrated HCl to the hollow CuSe aqueous dispersion described in step 4 is (0.01 mL to 0.02 mL): 50 mL; the stirring reaction time described in step 4 is 1 h to 3 h. The other steps are the same as those of specific embodiments 1 to 4.
[0060] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the mass ratio of PV3Mo9 to hollow CuSe in the hollow CuSe aqueous dispersion described in step 4 is (8 to 12): 1; the time for continuing the stirring reaction described in step 4 is 3h to 5h; in step 4, the precipitate is washed 3 to 5 times with deionized water and anhydrous ethanol respectively, and then dried at 55°C to 65°C for 10h to 14h to obtain PV3Mo9 / CuSe. The other steps are the same as those of specific embodiments 1 to 5.
[0061] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that: the concentration of the graphene oxide dispersion described in step 5 ① is 0.5g / L~1.5g / L; the concentration of the PV3Mo9 / CuSe dispersion described in step 5 ② is 4g / L~6g / L; the volume ratio of the graphene oxide dispersion described in step 5 ③ to the PV3Mo9 / CuSe dispersion is (0.5~1.5):(0.5~1.5); in step 5 ③, the graphene oxide dispersion is added to the PV3Mo9 / CuSe dispersion and stirred for 20h~28h; in step 5 ③, the mixed solution is heated to 140℃~160℃ and maintained for 0.5h~1.5h; in step 5 ③, the precipitated material is washed 3~5 times with deionized water and anhydrous ethanol respectively, and then dried at 55℃~65℃ for 10h~14h to obtain PV3Mo9 / CuSe@rGO. The other steps are the same as specific embodiments 1 to 6.
[0062] Specific embodiment eight: This embodiment is a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst for electrocatalytic CO2 reduction to prepare ethylene C 2+ product.
[0063] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst is used for electrocatalytic CO2 reduction to prepare ethylene-based C 2+ The product is completed by the following steps:
[0064] 1. Preparation of electrodes:
[0065] The isopropanol and the 5% by mass Nafion solution were ultrasonically mixed evenly, and then the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst was added, and the ultrasonication was continued for a period of time to obtain a slurry; the slurry was coated on the two surfaces of the carbon cloth, and then dried for a period of time to obtain a catalyst-coated carbon cloth, which is an electrode;
[0066] 2. Preparation of electrolyte:
[0067] ①, dissolving PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in KHCO3 solution to obtain cathode electrolyte;
[0068] ②, using H2SO4 solution with a concentration of 0.05mol / L to 0.15mol / L as the anolyte;
[0069] 3. Electrocatalytic CO2 reduction reaction:
[0070] A double-chamber electrolytic cell is used, the cathode chamber and the anode chamber are separated by a Nafion 117 proton exchange membrane, a cathode electrolyte is added to the cathode chamber, CO2 gas is introduced into the cathode electrolyte until CO2 is saturated; an anode electrolyte is added to the anode chamber, a three-electrode system is used, the electrode prepared in step 1 is used as the working electrode, Ag / AgCl is used as the reference electrode, and a Pt sheet is used as the auxiliary electrode, and constant potential electrolysis is performed to obtain gas phase products and liquid phase products; the gas phase products described in step 3 are CO, C2H4 and H2; the liquid phase product is C2H5OH. The other steps are the same as those in specific embodiments one to eight.
[0071] Specific embodiment ten: The difference between this embodiment and specific embodiments one to nine is that: the volume ratio of isopropanol described in step one to 5% Nafion solution is (480μL~520μL):(25μL~35μL); the volume ratio of the mass of PV3Mo9 coupled CuSe@rGO nanocomposite catalyst described in step one to 5% Nafion solution is (4mg~6mg):(25μL~35μL); the ultrasound is continued for 20min~40min in step one; the drying temperature in step one is 50℃~70℃, and the drying time is 4h~6h; the mass ratio of the slurry described in step one to the surface area of the carbon cloth is (5.0g~5.8g):(0.5cm 2 ~1.5cm 2); the concentration of the KHCO3 solution described in step 2① is 0.05mol / L~0.15mol / L; the concentration of the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in the cathode electrolyte described in step 2① is 1.000mmol / L~3.000mmol / L; the voltage of the constant potential electrolysis described in step 3 is –0.6~–1.4V (vs.RHE), and the electrolysis time is 0s~3600s. The other steps are the same as those in specific embodiments 1 to 9.
[0072] The following examples are used to verify the beneficial effects of the present invention:
[0073] Example 1: A method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst is specifically completed by the following steps:
[0074] 1. Preparation of polyoxometalate PV3Mo9:
[0075] ①, Na2HPO4 and Na2MoO4 are dissolved in deionized water, heated and stirred until boiling and maintained for a period of time, then NaVO3 aqueous solution is added, refluxed and heated for a period of time, cooled to room temperature, and the pH value of the solution is adjusted to acidic to obtain a reaction solution;
[0076] The mass volume ratio of Na2HPO4, Na2MoO4 and deionized water described in step 1① is 3.4g:21.8g:80mL;
[0077] In step 1①, heat and stir until boiling and keep for 0.5h;
[0078] The volume ratio of the NaVO3 aqueous solution to deionized water described in step 1① is 20mL:80mL;
[0079] The concentration of the NaVO3 aqueous solution described in step 1① is 0.2 g / mL;
[0080] The reflux heating time described in step 1① is 0.5h;
[0081] In step 1①, the pH value of the solution is adjusted to 2.5;
[0082] ② The reaction solution was transferred to a separatory funnel and extracted with anhydrous ether for multiple times. During the extraction process, dilute sulfuric acid was added until the water phase turned yellow, and the precipitated red oil droplets were collected. The extraction was repeated until the water phase turned light yellow, and then the ether was removed in a fume hood, and the polyoxometalate H6PV3Mo9O was obtained by concentration and crystallization. 40 , denoted as PV3Mo9;
[0083] The volume fraction of the dilute sulfuric acid described in step 1② is 50%;
[0084] 2. Preparation of Cu2O:
[0085] Cu(NO3)2 was added to ethylene glycol, stirred thoroughly until completely dissolved, and then transferred to a hydrothermal kettle, heated at 140°C for a period of time, and after cooling, the precipitate was separated by suction filtration, and the precipitate was washed and dried to obtain Cu2O;
[0086] The mass ratio of Cu(NO3)2 to ethylene glycol described in step 2 is 1g:80mL;
[0087] The heating time at 140° C. in step 2 is 180 min;
[0088] In step 2, the precipitate is washed 5 times with anhydrous ethanol and then dried at 60°C for 12 hours to obtain Cu2O;
[0089] 3. Preparation of hollow CuSe:
[0090] ①, add NaBH4 and selenium powder into deionized water, disperse evenly by ultrasonication to obtain solution A;
[0091] The mass volume ratio of NaBH4, selenium powder and deionized water described in step 3① is 0.038g:0.079g:100mL;
[0092] ②, dispersing Cu2O in water to obtain a Cu2O aqueous dispersion; adding solution A to the ultrasonically dispersed Cu2O aqueous dispersion, ultrasonically stirring and reacting for a period of time, and then centrifuging to obtain a precipitate; washing the precipitate, and then drying to obtain a hollow CuSe;
[0093] The concentration of the Cu2O aqueous dispersion described in step 3② is 0.01 mol / L;
[0094] The volume ratio of solution A described in step 3② to Cu2O aqueous dispersion is 1:1;
[0095] The ultrasonic and stirring reaction time in step 3② is 1 hour;
[0096] In step 3②, the precipitate is washed five times with deionized water and anhydrous ethanol, and then dried at 60°C for 12 hours to obtain a hollow CuSe.
[0097] 4. Preparation of PV3Mo9 / CuSe:
[0098] The hollow CuSe is dispersed in water to obtain a hollow CuSe aqueous dispersion; concentrated HCl is added dropwise to the hollow CuSe aqueous dispersion, stirred and reacted for a period of time, and then PV3Mo9 is added, and the stirring and reaction is continued for a period of time, and then centrifuged to obtain a precipitate; the precipitate is washed and then dried to obtain a PV3Mo9 / CuSe powder;
[0099] The concentration of the hollow CuSe aqueous dispersion described in step 4 is 0.001 g / mL;
[0100] The mass fraction of concentrated HCl in step 4 is 37%;
[0101] The volume ratio of concentrated HCl to the hollow CuSe aqueous dispersion described in step 4 is 0.015 mL:50 mL;
[0102] The stirring reaction time in step 4 is 2h;
[0103] The mass ratio of PV3Mo9 described in step 4 to the hollow CuSe in the hollow CuSe aqueous dispersion is 10:1;
[0104] The stirring reaction time in step 4 is 4 hours;
[0105] In step 4, the precipitated material is washed 5 times with deionized water and anhydrous ethanol respectively, and then dried at 60° C. for 12 h to obtain PV3Mo9 / CuSe;
[0106] 5. Preparation of PV3Mo9 / CuSe@rGO:
[0107] ①, dispersing graphene oxide in water to obtain a graphene oxide dispersion;
[0108] The concentration of the graphene oxide dispersion described in step 5① is 1 g / L;
[0109] ②, dispersing PV3Mo9 / CuSe powder into water to obtain PV3Mo9 / CuSe dispersion;
[0110] The concentration of the PV3Mo9 / CuSe dispersion described in step 5② is 5 g / L;
[0111] ③. Add the graphene oxide dispersion to the PV3Mo9 / CuSe dispersion and stir for a period of time to obtain a mixed solution; heat the mixed solution to 150°C and keep it for a period of time, centrifuge and separate to obtain a precipitate; wash the precipitate and dry it to obtain PV3Mo9 / CuSe@rGO, which is a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst;
[0112] The volume ratio of the graphene oxide dispersion and the PV3Mo9 / CuSe dispersion described in step 5③ is 1:1;
[0113] In step 5③, the graphene oxide dispersion is added to the PV3Mo9 / CuSe dispersion and stirred for 24 hours;
[0114] In step 5③, the mixed solution is heated to 150°C and maintained for 1 hour;
[0115] In step 5③, the precipitated material was washed 5 times with deionized water and anhydrous ethanol respectively, and then dried at 60°C for 12h to obtain PV3Mo9 / CuSe@rGO.
[0116] Application Example 1: Preparation of ethylene-based C using a PV3Mo9-coupled CuSe@rGO nanocomposite catalyst prepared in Example 1 for electrocatalytic CO2 reduction 2+ The product is completed by the following steps:
[0117] 1. Preparation of electrodes:
[0118] 500 μL of isopropanol and 30 μL of 5% Nafion solution were ultrasonically mixed, and then 5 mg of V3Mo9 coupled CuSe@rGO nanocomposite catalyst was added, and the ultrasonic treatment was continued for 30 min. The slurry was coated on both surfaces of 1 cm × 1 cm carbon cloth, and then dried at 60 ° C for 5 h to obtain catalyst-coated carbon cloth, which is the electrode.
[0119] 2. Preparation of electrolyte:
[0120] ①, dissolving the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in a KHCO3 solution with a concentration of 0.1 mol / L to obtain a cathode electrolyte;
[0121] The concentration of PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in the cathode electrolyte described in step 2① is 2.000mmol / L;
[0122] ②, use H2SO4 solution with a concentration of 0.1mol / L as the anolyte;
[0123] 3. Electrocatalytic CO2 reduction reaction:
[0124] A double-chamber electrolytic cell was used, in which the cathode chamber and the anode chamber were separated by a Nafion 117 proton exchange membrane. A cathode electrolyte was added to the cathode chamber, and CO2 gas was introduced into the cathode electrolyte until CO2 was saturated. Anode electrolyte was added to the anode chamber, and a three-electrode system was used, with the electrode prepared in step 1 as the working electrode, Ag / AgCl as the reference electrode, and Pt sheet as the auxiliary electrode, to perform constant potential electrolysis to obtain gas phase products and liquid phase products. The gas phase products were analyzed by gas chromatography, and the liquid phase products were detected by liquid phase nuclear magnetic hydrogen spectrum. Combined with the detection results, the distribution of ECO2RR electrolysis products and FE were evaluated.
[0125] The voltages of the constant potential electrolysis described in step 3 are -0.6 V (vs. RHE), -0.8 V (vs. RHE), -1.0 V (vs. RHE), -1.2 V (vs. RHE) and -1.4 V (vs. RHE), and the electrolysis time is 3600 s;
[0126] The gas phase products described in step 3 are CO, C2H4 and H2; the liquid phase product is C2H5OH.
[0127] Figure 1 The scanning electron microscope images of CuSe and PV3Mo9 / CuSe@rGO prepared in Example 1, in which (a) is CuSe, (b) is PV3Mo9 / CuSe@rGO (300nm), and (c) is PV3Mo9 / CuSe@rGO (2μm);
[0128] like Figure 1 (a) shows that the hollow spherical structure of CuSe can be clearly seen. Figure 1 (b) is PV3Mo9 / CuSe@rGO. It is obvious that there is a film between the catalysts, indicating that the catalyst and rGO are well combined. Figure 1 (c) is PV3Mo9 / CuSe@rGO at 2μm scale. It can be seen that the catalyst has good dispersion, and the morphology shows that CuSe is successfully loaded on rGO.
[0129] The FTIR of PV3Mo9 and PV3Mo9 / CuSe@rGO was explored, such as Figure 2 As shown;
[0130] Figure 2 is the Fourier transform infrared spectra of PV3Mo9 and PV3Mo9 / CuSe@rGO prepared in Example 1;
[0131] Figure 2 The results show that at 1065cm -1 、947cm -1 、865cm -1 and 785cm -1The four characteristic peaks unique to POM materials appeared on PV3Mo9 / CuSe@rGO, indicating that PV3Mo9 successfully modified the catalyst.
[0132] The X-ray powder diffraction patterns of PV3Mo9 / CuSe@rGO and CuSe were investigated. Figure 3 As shown;
[0133] Figure 3 is the X-ray powder diffraction pattern of PV3Mo9 / CuSe@rGO and CuSe prepared in Example 1;
[0134] Depend on Figure 3 It can be seen that CuSe is consistent with the PDF standard card, indicating that it was successfully prepared. However, the prepared PV3Mo9 / CuSe@rGO catalyst only shows obvious diffraction peaks at 2θ=28° and 2θ=36°, and the weakening of other diffraction peaks indicates that the crystallinity of the modified material has deteriorated, which is caused by the POM loading and rGO substrate.
[0135] Depend on Figures 1 to 3 It can be seen that the catalyst was successfully prepared.
[0136] Figure 4 The linear voltammetric curve of PV3Mo9 / CuSe@rGO prepared in Example 1 in 0.1M KHCO3 solution under different atmospheres (Ar / CO2);
[0137] like Figure 4 As shown: Compared with the Ar environment, the current density of the LSV curve in the CO2 environment is significantly increased, which indicates that the synthesized PV3Mo9 / CuSe@rGO catalyst has high electrochemical activity for ECO2RR and can be used as a catalyst for ECO2RR.
[0138] Figure 5 is a gas chromatogram of the gas phase product of PV3Mo9 / CuSe@rGO prepared in Example 1 in Application Example 1 after electrolysis at -1.0V (vs.RHE) for 1h;
[0139] from Figure 5 It can be seen that CO and C2H4 are detected by the FTD detector, and H2 is detected by the TCD detector, indicating that CO, C2H4 and H2 are generated in the system.
[0140] Figure 6 is the nuclear magnetic hydrogen spectrum of the cathode liquid of PV3Mo9 / CuSe@rGO prepared in Example 1 in Application Example 1 after electrolysis at -1.0V (vs.RHE) for 1h;
[0141] Depend on Figure 6It can be seen that ethanol was detected in the cathode liquid, indicating that the system produced ethanol during the electrolysis process.
[0142] Figure 7 It is the FE of each product of CuSe, PV3Mo9 / CuSe and PV3Mo9 / CuSe@rGO prepared by Example 1 in Application Examples 1 to 3 after electrolysis for 1 h in the electrolysis range of –0.6 to –1.4 V (vs. RHE), in which (a) is CuSe; (b) is PV3Mo9 / CuSe; (c) is PV3Mo9 / CuSe@rGO;
[0143] from Figure 7 (a) It can be seen that when CuSe is used as a catalyst, no ethylene is produced, and the FE of H2 is very high in the potential range of –0.6 to –1.4 V (vs. RHE). Figure 7 (b) It can be seen that when PV3Mo9 / CuSe is used as a catalyst, ethylene is produced, but the FE of ethylene is not high at this time, and in the potential range of -0.6 to -1.4 V (vs. RHE), the FE of H2 decreases but is still very high. Figure 7 (c) It can be seen that when PV3Mo9 / CuSe@rGO is used as a catalyst, the FE of ethylene is significantly increased and the FE of H2 is significantly reduced. At -1.2V (vs. RHE), the FE of ethylene reaches a maximum of 75.9%, while the FE of H2 is the minimum at 2.1%.
[0144] Figure 8 It curves obtained after electrolysis of CuSe, PV3Mo9 / CuSe and PV3Mo9 / CuSe@rGO prepared in Example 1 in Examples 1 to 3 at -0.6 to -1.4 V (vs. RHE) for 1 h, in which (a) is CuSe; (b) is PV3Mo9 / CuSe; (c) is PV3Mo9 / CuSe@rGO;
[0145] Depend on Figure 8 As shown in (a) and (b), at –1.4 V (vs. RHE), the stability of CuSe and PV3Mo9 / CuSe systems was poor during the 3600 s electrolysis process. Figure 8 (c) It can be seen that within the electrolysis range of –0.6 to –1.4 V (vs. RHE), the PV3Mo9 / CuSe@rGO system maintains high stability during the electrolysis process of 3600 s.
[0146] Fig. 9 The AC impedance diagram of PV3Mo9 / CuSe@rGO prepared in Example 1 in 0.1M KHCO3 solution under different atmospheres (Ar / CO2);
[0147] Depend on Fig. 9 It can be seen that in the CO2 environment, the smaller radius of curvature of the Niquist curve reflects the significant reduction in electrochemical impedance, which indicates that the electron transfer process is faster in this environment. This feature is positively correlated with the high Faraday efficiency of ethylene production in the PV3Mo9 / CuSe@rGO system. Since the formation of ethylene molecules consumes up to 12 electrons, far more than the 2 electrons required for the generation of CO and H2, rapid electron transfer becomes the key, which can effectively reduce the desorption of *CO intermediates, thereby improving the selectivity of ethylene products. In short, in a low-impedance CO2 environment, efficient electron transfer is achieved, which is conducive to the highly selective synthesis of ethylene on the PV3Mo9 / CuSe@rGO catalyst.
Claims
1. A method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of polyoxometalate PV3Mo9: ①, Na2HPO4 and Na2MoO4 are dissolved in deionized water, heated and stirred until boiling and maintained for a period of time, then NaVO3 aqueous solution is added, refluxed and heated for a period of time, cooled to room temperature, and the pH value of the solution is adjusted to acidic to obtain a reaction solution; ② The reaction solution was transferred to a separatory funnel and extracted with anhydrous ether for multiple times. During the extraction process, dilute sulfuric acid was added until the water phase turned yellow, and the precipitated red oil droplets were collected. The extraction was repeated until the water phase turned light yellow, and then the ether was removed in a fume hood, and the polyoxometalate H6PV3Mo9O was obtained by concentration and crystallization. 40 , denoted as PV3Mo9; 2. Preparation of Cu2O: Cu(NO3)2 is added to ethylene glycol, stirred until completely dissolved, and then transferred to a hydrothermal kettle, heated at 120°C to 160°C for a period of time, and after cooling, the precipitate is separated by suction filtration, and the precipitate is washed and dried to obtain Cu2O; 3. Preparation of hollow CuSe: ①, add NaBH4 and selenium powder into deionized water, disperse evenly by ultrasonication to obtain solution A; ②, dispersing Cu2O in water to obtain a Cu2O aqueous dispersion; adding solution A to the ultrasonically dispersed Cu2O aqueous dispersion, ultrasonically stirring and reacting for a period of time, and then centrifuging to obtain a precipitate; washing the precipitate, and then drying to obtain a hollow CuSe; 4. Preparation of PV3Mo9 / CuSe: The hollow CuSe is dispersed in water to obtain a hollow CuSe aqueous dispersion; concentrated HCl is added dropwise to the hollow CuSe aqueous dispersion, stirred and reacted for a period of time, and then PV3Mo9 is added, and the stirring and reaction is continued for a period of time, and then centrifuged to obtain a precipitate; the precipitate is washed and then dried to obtain a PV3Mo9 / CuSe powder; 5. Preparation of PV3Mo9 / CuSe@rGO: ①, dispersing graphene oxide in water to obtain a graphene oxide dispersion; ②, dispersing PV3Mo9 / CuSe powder into water to obtain PV3Mo9 / CuSe dispersion; ③. Add the graphene oxide dispersion to the PV3Mo9 / CuSe dispersion and stir for a period of time to obtain a mixed solution; heat the mixed solution to 140°C to 160°C and maintain for a period of time, centrifuge and obtain a precipitate; wash the precipitate and dry it to obtain PV3Mo9 / CuSe@rGO, which is a PV3Mo9-coupled CuSe@rGO nanocomposite catalyst.
2. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The mass volume ratio of Na2HPO4, Na2MoO4 and deionized water described in step 1① is (3.2g~3.6g):(21.6g~22.0g):(70mL~90mL); the time of heating and stirring to boiling and maintaining in step 1① is 0.5h~1h; the volume ratio of NaVO3 aqueous solution described in step 1① to deionized water is 20:(70~90); the concentration of NaVO3 aqueous solution described in step 1① is 0.2g / mL~0.3g / mL; the reflux heating time described in step 1① is 0.5h~1h; the pH value of the solution is adjusted to 2.4~2.6 in step 1①; the volume fraction of dilute sulfuric acid described in step 1② is 50%.
3. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The mass ratio of Cu(NO3)2 described in step 2 to the volume ratio of ethylene glycol is 1g:(70mL~90mL); the heating time at 120℃~160℃ in step 2 is 160min~200min; in step 2, the precipitate is washed 3~5 times with anhydrous ethanol, and then dried at 55℃~65℃ for 10h~14h to obtain Cu2O.
4. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The mass volume ratio of NaBH4, selenium powder and deionized water described in step 3① is (0.03g~0.04g):(0.07g~0.08g):100mL; the concentration of the Cu2O aqueous dispersion described in step 3② is 0.005mol / L~0.015mol / L; the volume ratio of solution A and Cu2O aqueous dispersion described in step 3② is (0.5~1.5):(0.5~1.5); the ultrasonic and stirring reaction time described in step 3② is 0.5h~5h; in step 3②, the precipitated material is washed 3 to 5 times with deionized water and anhydrous ethanol in turn, and then dried at 55℃~65℃ for 10h~14h to obtain hollow CuSe.
5. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The concentration of the hollow CuSe aqueous dispersion described in step 4 is 0.001 g / mL to 0.002 g / mL; the mass fraction of the concentrated HCl described in step 4 is 36% to 38%; the volume ratio of the concentrated HCl to the hollow CuSe aqueous dispersion described in step 4 is (0.01 mL to 0.02 mL): 50 mL; the stirring reaction time described in step 4 is 1 h to 3 h.
6. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The mass ratio of PV3Mo9 and hollow CuSe in the hollow CuSe aqueous dispersion described in step 4 is (8-12):1; the time for continuing the stirring reaction described in step 4 is 3h-5h; in step 4, the precipitated material is washed 3-5 times with deionized water and anhydrous ethanol respectively, and then dried at 55°C-65°C for 10h-14h to obtain PV3Mo9 / CuSe.
7. The method for preparing a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 1, characterized in that The concentration of the graphene oxide dispersion described in step five ① is 0.5g / L~1.5g / L; the concentration of the PV3Mo9 / CuSe dispersion described in step five ② is 4g / L~6g / L; the volume ratio of the graphene oxide dispersion and the PV3Mo9 / CuSe dispersion described in step five ③ is (0.5~1.5):(0.5~1.5); in step five ③, the graphene oxide dispersion is added to the PV3Mo9 / CuSe dispersion and stirred for 20h~28h; in step five ③, the mixed solution is heated to 140℃~160℃ and maintained for 0.5h~1.5h; in step five ③, the precipitated material is washed 3~5 times with deionized water and anhydrous ethanol respectively, and then dried at 55℃~65℃ for 10h~14h to obtain PV3Mo9 / CuSe@rGO.
8. Use of a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst prepared by the preparation method according to claim 1, characterized in that A PV3Mo9 coupled CuSe@rGO nanocomposite catalyst for electrocatalytic CO2 reduction to ethylene-based C 2+ product.
9. The use of a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 8, characterized in that A PV3Mo9 coupled CuSe@rGO nanocomposite catalyst for electrocatalytic CO2 reduction to ethylene-based C 2+ The product is completed by the following steps:
1. Preparation of electrodes: The isopropanol and the 5% by mass Nafion solution were ultrasonically mixed evenly, and then the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst was added, and the ultrasonication was continued for a period of time to obtain a slurry; the slurry was coated on the two surfaces of the carbon cloth, and then dried for a period of time to obtain a catalyst-coated carbon cloth, which is an electrode; 2. Preparation of electrolyte: ①, dissolving PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in KHCO3 solution to obtain cathode electrolyte; ②, using H2SO4 solution with a concentration of 0.05mol / L to 0.15mol / L as the anolyte; 3. Electrocatalytic CO2 reduction reaction: A double-chamber electrolytic cell is used, wherein the cathode chamber and the anode chamber are separated by a Nafion 117 proton exchange membrane, a cathode electrolyte is added to the cathode chamber, and CO2 gas is introduced into the cathode electrolyte until the CO2 is saturated; an anode electrolyte is added to the anode chamber, and a three-electrode system is used, wherein the electrode prepared in step 1 is used as a working electrode, Ag / AgCl is used as a reference electrode, and a Pt sheet is used as an auxiliary electrode, and constant potential electrolysis is performed to obtain gas phase products and liquid phase products; The gas phase products described in step 3 are CO, C2H4 and H2; the liquid phase product is C2H5OH.
10. The use of a PV3Mo9 coupled CuSe@rGO nanocomposite catalyst according to claim 8, characterized in that The volume ratio of isopropanol described in step 1 to 5% Nafion solution is (480μL~520μL):(25μL~35μL); the volume ratio of the mass of PV3Mo9 coupled CuSe@rGO nanocomposite catalyst described in step 1 to 5% Nafion solution is (4mg~6mg):(25μL~35μL); the ultrasonic treatment is continued for 20min~40min in step 1; the drying temperature in step 1 is 50℃~70℃, and the drying time is 4h~6h; the mass ratio of the slurry described in step 1 to the surface area of the carbon cloth is (5.0g~5.8g):(0.5cm 2 ~1.5cm 2 ); the concentration of the KHCO3 solution described in step 2① is 0.05mol / L~0.15mol / L; the concentration of the PV3Mo9 coupled CuSe@rGO nanocomposite catalyst in the cathode electrolyte described in step 2① is 1.000mmol / L~3.000mmol / L; the voltage of the constant potential electrolysis described in step 3 is –0.6~–1.4V (vs.RHE), and the electrolysis time is 0s~3600s.
Citation Information
Patent Citations
Preparation method of CuSe catalyst for electrocatalytic CO2 reduction
CN114196982A
Bimetal sulfide catalyst, preparation method thereof and low-energy-consumption method for preparing high-proportion H2 / CO synthesis gas by using bimetallic sulfide catalyst
CN116988091A